2020
DOI: 10.1016/j.jhep.2020.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome activation and pyroptosis in lymphopenic liver patients with COVID-19

Abstract: supplementary data for Table S1, reviewed data of all previous cases. CMB made a critical revision of the manuscript, helped in the acquisition of data, provided supplementary data for Table S1, reviewed data of all previous cases. All authors revised and gave the approval of the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 10 publications
3
40
0
Order By: Relevance
“…Several clinical studies showed that increased inflammasome activity leads to immune dysregulation and ultimately severe disease for COVID-19 patients (11)(12)(13). A recent study directly demonstrates that the NLRP3 inflammasome is activated in response to SARS-CoV-2 infection (14).…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical studies showed that increased inflammasome activity leads to immune dysregulation and ultimately severe disease for COVID-19 patients (11)(12)(13). A recent study directly demonstrates that the NLRP3 inflammasome is activated in response to SARS-CoV-2 infection (14).…”
Section: Introductionmentioning
confidence: 99%
“…Preventing the pyroptotic lymphocyte death by using caspase inhibitors may lead to better success rather than inhibition of the inflammatory response from the cell death itself. The failure of cytokine targeted therapies could be due to that adaptive immune dysfunction due to AVID weighing more heavily than an inflammatory response in disease progression (18).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammasome activation in peripheral immune cells and tissues was recently observed in COVID-19 patients and the level of inflammasome-derived products, including active caspase-1, associated with disease severity and poor outcomes (17). We recently reported that caspase-1 expression in lymphocytes and serum IL-18 levels are increased in liver transplant patients acutely ill with SARS-CoV-2 infection suggesting pyroptosis mechanisms may play role in severe COVID-19 (18). A recent study showed that SARS-CoV-2 infection of rhesus macaques led to an upregulation of caspase-1 molecular signature in peripheral blood cells as early as day 2 post-inoculation (19).…”
Section: Introductionmentioning
confidence: 99%
“…The end result is likely a self-damaging cell death and subsequent cytokine storm that further fuels the inflammation created by the viral infection, resulting in AVID. The failure of cytokine targeted therapies could be due to that adaptive immune dysfunction weighs more heavily than an inflammatory response in disease progression (15). This connection between caspase-1 and COVID-19 has significant therapeutic implications since preventing the pyroptotic lymphocyte death rather than inhibition of the inflammatory response may be a more efficacious therapeutic option.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that caspase-1 expression in lymphocytes and serum IL-18 levels are increased in liver transplant patients acutely ill with SARS-CoV-2 infection, along with non-liver transplant controls, suggesting pyroptosis mechanisms may play role in severe COVID-19 (15). A recent study showed that SARS-CoV-2 infection of rhesus macaques led to an upregulation of caspase-1 molecular signature in peripheral blood cells as early as day 2 post-inoculation (16).…”
Section: Introductionmentioning
confidence: 99%